The Effect of Gainesville's Urban Trees on Energy Use of Residential Buildings - Francisco Escobedo; Jennifer A. Seitz; Wayne Zipperer (EDIS, 2009)
FOR-211, a 3-page fact sheet by Francisco Escobedo, Jennifer A. Seitz, and Wayne Zipperer, summarizes the results of a study to estimate urban tree heating and cooling effects on residential buildings in Gainesville, Florida. Includes references. Published by the UF School of Forest Resources and Conservation, March 2009.